MICROVASCULAR COMPLICATION PROFILE IN T2DM PATIENTS AT SURABAYA TERTIARY HOSPITAL - Ardiany, Deasy; Wibisono, Sony; Pranoto, Agung (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION Chronic hyperglycemia in diabetes leads to organ dysfunction arising directly or indirectly. The chronic complications of diabetes are traditionally classified as macro- or microvascular, depending on the underlying pathophysiology. Retinopathy, nephropathy and neuropathy are microvascular complications of diabetes that may initially present subclinically. This study aims to examine the prevalence of diabetes-related microvascular disease. METHODOLOGY This was a cross-sectional observational study performed at the diabetes outpatient clinic of Dr. Soetomo General Hospital, carried out from July to December 2019. All participants underwent complete history taking and physical examination. Glycosylated hemoglobin (HbA1c) levels, glomerular filtration rate estimation (eGFR), and urinalysis parameters were collected from all subjects. RESULTS This study involved 100 T2DM patients consisting of 68 (40%) males and 100 (60%) females with an average age of 54.8 years. The average duration of diabetes is 6.65 years. The proportion of patients with HbA1c greater than seven was 68% (115 patients), and the rest had HbA1c of less than 7% (53 patients). Fifty-two patients (31%) had a normal eGFR, and 116 (69%) patients had an eGFR less than 60 ml/min/1.73m2. Proteinuria was found in 125 (74%) patients, whereas the remaining 43 patients (26%) had no proteinuria. Eighty subjects (48%) had diabetic retinopathy, with a PDR proportion of 19% (32 subjects). CONCLUSION The prevalence of microvascular complications, namely diabetic kidney disease and diabetic retinopathy, is still frequent in this study. This study also shows that most patients have not achieved optimal glycemic control.